EFFECT OF INTERNET DEPENDENCY ON THE STUDY SKILLS OF THE UNDERGRADUATE DENTAL STUDENTS - R. , Swetha; L., Keerthi Sasanka; Premavathy, Dinesh (International Journal of Psychosocial Rehabilitation, 2020)
Aim: To analyse the effect of internet dependency on the study skills of the undergraduate dental students. Methods and Materials: An online survey among 100 undergraduate dental students was conducted to analyze internet usage and its dependency on study skills. Self-administered questionnaires (set of 10) were circulated through the WhatsApp platform. The study was carried out from May 2020 to June 2020. The participants were explained about the purpose of the study in detail. They were advised to read the questions carefully and then begin to fill out the survey. The data were validated and verified. Feedback and corrections from the participants were taken into account. The results were statistically analysed Results: On analysing the data, 34% of the students spent more than 5 hours on the internet, 56% preferred the internet over a book for studying, 62% of the participants preferred the internet to find solutions quicker; the majority of the participants, i.e., 62%, accepted that their academic performance would improve with the help of the internet, 65% of the participants felt that the internet was beneficial during lockdown, 43% agreed that the internet helped during the lockdown in attending virtual classes, for 31% it helped to stay in touch with the course, and for 26% of the participants it helped in conducting surveys and doing research. Conclusion: There are several benefits of the internet. The students should be trained to improve their strategic browsing, which can help broaden their internet usage. There are both positive and negative sides to using the internet. Balanced use of the internet among the students would help them in scoring more marks, thus better academic performance.